PESQUISA EM ENSINO DE ZOOLOGIA: o que produzem as Pós-Graduações brasileiras? - AVIZ, Jesiel Oliveira de (2024)
This study conducts a comprehensive analysis of the current state of zoology teaching in Brazil, based on 65 Master's dissertations and Doctoral theses spanning the period from 1995 to 2022. The survey of these theses aims to understand potential temporal and geographical trends and their main focuses. The study highlights a notable increase in academic production in the last five years, especially in 2019 and 2020, indicating a growing interest in the field. The Southeast region leads in the number of productions, followed by the Northeast, revealing geographical disparities in research within this domain. The analysis indicates that the majority of research was conducted in public institutions, emphasizing the crucial role of the state in promoting scientific production. Research from these theses on zoology teaching predominantly focuses on high school, with over half of the studies investigating students' conceptions and perceptions, providing valuable insights into the educational needs of this group. The significant growth of Professional Master's programs since 2016 suggests a more equitable distribution of research across the country. However, there is a notable absence of doctoral research in the area, pointing to possible structural or interest-related challenges at this academic level. The qualitative analysis of abstracts reveals that research also explores different educational environments, with almost half taking place in 'non-formal' settings. This diversified approach demonstrates the importance given to the use of spaces such as museums and science centers to enhance zoology teaching. In summary, this study not only provides an overview of the current landscape of zoology teaching in Brazil but also highlights areas of emphasis and gaps in research, contributing to future educational strategies and more informed and effective public policies.